FATIGUE FAILURE IN A LONGITUDINAL WELDED ELBOW OF A PROCESSING VESSEL - D.N. Adnyana (National Research and Innovation Agency (BRIN), 2021)
A longitudinal welded elbow made of austenitic stainless steel type 316 and used as a drain line on a processing vessel had suffered damage (leakage) after it had only been in operation for a few years. Process fluid that was drained out of the vessel consists of fatty acid containing hydrogen gas at a temperature of 150°C and a pressure of 60 bar(g). Initially, the drain process was carried out only once a year, but recently due to frequent changes in the types of product being made, the frequency of drain process has increased to several times a month. This study aims to determine the type and factors that have caused leakage in the elbow. Metallurgical assessment was carried out by preparing a number of specimens from the leaking elbow. A number of laboratory examinations were performed including visual and macroscopic tests, chemical composition analysis, metallographic examination, hardness tests and scanning electron microscopy (SEM) equipped with energy-dispersive spectroscopy (EDS) analysis. The results obtained indicate that the leaking elbow has experienced fatigue failure due to cyclic loadings caused by the increasing frequency of the number of drain processes carried out through the elbow. The factor causing fatigue failure at the elbow is likely due to welding defect of imperfect shape that formed on the inner wall of the elbow around the HAZ (heat-affected zone)/fusion boundary, and causing high stress concentrations in that area.